Leptin-to-adiponectin ratio in obese adolescents with nonalcoholic fatty liver disease - Angın, Yeliz; Arslan, Nur; Kuralay, Filiz (The Turkish Journal of Pediatrics, 2014)
The leptin-to-adiponectin (L/A) ratio has been used to show insulin resistance (IR) in recent years. The aim of this study was to investigate the L/A ratio in obese adolescents and compare this ratio in patients with and without nonalcoholic fatty liver disease (NAFLD) and also with healthy controls. The second aim was to search the possible correlations between the L/A ratio with the markers of IR and inflammation. A total of 47 obese (mean age: 13.1±2.1 years) and 19 healthy children (mean age: 13.8±0.3 years) were included in the study. The presence of fatty liver was identified by ultrasonography. Cases were divided into three groups as NAFLD (+) and NAFLD (-) obese patients and controls. Liver biochemistries, insulin and serum lipids, C-reactive protein, tumor necrosis factor-alpha (TNF-alpha), interleukin-6, adiponectin, and leptin were determined. The L/A ratio was calculated. IR was estimated according to the homeostasis model assessment of insulin resistance (HOMA-IR). The L/A ratio was significantly higher in NAFLD (+) patients than in the other two groups, and in NAFLD (-) patients than the healthy peers. Moreover, L/A ratio correlated more strongly with weight for height (r: 0.528, p